Comparison of Prognostic Scores in Chronic Myeloid Leukemia (Cml) Patients with Bcr-Abl Mutation Types B3a2 and B2a2 in Dr. Sardjito General Hospital - Nina Mulyani; Johan Kurnianda; Mardiah Suci Hardianti (Faculty of Medicine Universitas Gadjah Mada, 2020)
Background. Chronic Myeloid Leukemia (CML) is a myeloproliperative malignancy that is caused byreciprocal translocation between chromosomes 9 and 22 which form the BCR-ABL fusion gene. Most CML patients have a major type of BCR-ABL mutation. There are b3a2 and b2a2 types, which produce different oncoproteins in 25 amino acid elements. The expression of different proteins is thought to cause differences in clinical manifestations, laboratory, and prognosis. In CML, there are several prognostic scoring systems, including Sokal, Hasford, andEUTOS scores which combine clinical and laboratory parameters. The effect of this genomic breakpoint location on clinical and biological characteristics is still controversial.Aims. The aim of this study was to determine the comparison of prognostic scores between CML patients with b3a2 and b2a2 BCR-ABL mutation types in Dr. Sardjito General Hospital.Methods. This study was a cross sectional retrospective study used secondary data from medical records of Dr. Sardjito General Hospital, from March 2014 to April 2016. The prognostic score of Sokal, Hasford, and EUTOS was calculated in the BCR-ABL mutation type groups b3a2 and b2a2. Data were analyzed by Chi Square test.Results. A total of 113 CML patients were analyzed with 74 (65.5%) b3a2 mutation type groups and 39 (34.5%) b2a2 mutation type groups. Hemoglobin levels, leukocytes, platelets, basophils, and eosinophils did not differ significantly between the two groups of mutation types. Meanwhile, the statistical test for the phase of disease when the patient was first diagnosed in both types of mutations showed a significant difference (p = 0.005). More patients with types of b2a2 mutations came in the acceleration and blast crisis phases than b3a2 types. However, Sokal, Hasford, and EUTOS prognostic scores in the b3a2 mutation type group were not significantly different from the b2a2 group (p> 0.05).Conclusions. There was no significant difference in prognostic scores of CML patients with the b3a2 BCRABL mutation type compared with the b2a2 mutation type in Dr. Sardjito General Hospital Yogyakarta.